An Automatic System to Grade Multiple Choice Questions paper based exams - Ammar Awny Abbas (مجلة جامعة الانبار للعلوم الصرفة, 2009)
Abstract:The use of Multiple Choice Question (MCQ) in paper based exams is a very popular choice in the international certificate exams (like TOEFL) because it is very fast to grade and it does not let the student write any unnecessary information. In international tests, a specialized machine is used for grading MCQ paper based exams, this machine is very expensive and it needs a special trained operator to operate the machine correctly and efficiently. This project suggests a method to use a personal computer plus a scanner and a program written in Matlab programming language to grade a specially designed MCQ exam test paper with 15 questions with four choices for each question which the student can choose only one answer per question. The program has been tested to detect the correct answers by comparing each paper with a pre scanned test paper that contains the correct answers, many forms of test papers are used to answer different sets real questions for a real exam that has been conducted in the computer center in the Baghdad University and shown to produce results that matches the results gained from grading the same papers manually. The program is written in such a way that it can tolerate rotating the papers in the scanning operation using the process of image registration, any kind of pencil can be used to make the correct answer no matter its color. The program can detect question with multiple choices and eliminate them from calculations.